A Review The Role of Maggot Debridement Therapy in Wound Healing (International Journal of Scientific Research and Management (IJSRM), 2022)
Abstract The upward trend of diabetes and its complications had taken a big toll on developing countries where big budgets are allocated to manage it. Diabetes-based foot ulcerations has become a nightmare for patients and equally the clinicians due to its chronicity and devastating complications. Diabetic foot ulcers (DFU) take a long time to heal and generally resistant to conventional methods. DFU are commonly associated with high numbers of foot complications such as infection, gangrene and lower limb amputations. Despite the technological advancement in chronic wound management, the numbers of preventable foot complications especially amputations of toes and limb are still in the upward trend as the number of diabetics increases across the globe. Alternative method using sterile maggots of Lucilia spp has been much talked about for the past few decades to improve wound healing outcomes and ultimately reduce foot complications. Maggot debridement therapy, commonly known as MDT has been widely used as an alternative tool in the debridement of chronic wounds to remove slough, necrotic tissue from the wound bed. The usage of MDT has produced significant debridement and healing outcomes in diabetic foot ulcers and has been shown to reduce infections and stimulate healing. Despite numerous findings pointing to the relevance of MDT in the treatment protocol of chronic wounds especially DFU, MDT remains as the last resort in the process of salvaging limbs.